KELAYAKAN MEDIA BUKU SAKU PANDUAN LAPANGAN MATERI JAMUR DI KELAS X SMA - Nursamsiyah, Nursamsiyah; Yeni, Laili Fitri (FKIP Universitas Tanjungpura, 2024)
The field guide pocket book is a small book that can be put in a pocket so that it is easy to carry anywhere. This field guide pocket book contains pictures of tools and materials, criteria for mushroom morphology, making wet and dry herbariums and how to work when out in the field. This study aims to determine the feasibility of a field guide pocket book based on the results of an inventory of macroscopic fungi found in the Mount Temenggung Protection Forest, Ketapang Regency. The research instrument used is a validation sheet which includes aspects of format, content, language, and effectiveness. This field guide pocket book media was tested for feasibility by five validators, 2 validators from biology lecturers from FKIP Untan and 3 validators from high school/vocational high school biology teachers. The results of this study indicate that the field guide pocket book validation was carried out by five validators with a CVI (Content Validity Index) value of 0.99 which was declared feasible. Based on the results of the validation, it can be concluded that the field guide pocket book on the class X mushroom classification sub-material of high school/vocational high school is declared suitable to be used as a learning medium.Kata Kunci: Field Guide Pocket Book, Inventory, Fungi, Instrument